Fermented Astragalus membranaceus could promote the liver and intestinal health of juvenile tiger grouper (Epinephelus fuscoguttatus) - Yang, Jingru; Zhou, Shengjie; Fu, Zhengyi; Xiao, Bo; Li, Minghao; Yu, Gang; Ma, Zhenhua; Zong, Humin (Frontiers in Physiology, 2023)
In order to understand the effects of fermented Astragalus membranaceus (FAM) on the liver and intestinal health of tiger grouper (Epinephelus fuscoguttatus), this study was conducted. This study evaluates the effects of different levels of FAM on liver and intestinal tissue structure, serum biochemical parameters, intestinal digestive enzyme, and microbiota structure of tiger grouper. Fish were fed with diets (crude protein ≥ 48.0%, crude fat ≥ 10.0%) with five levels of FAM (L1:0.25%, L2: 0.5%, L3: 1%, L4: 2% and L5: 4%) in the experimental groups and a regular diet was used as the control (L0: 0%) for 8 weeks. Compared with AM, the protein content of FAM was significantly changed by 34.70%, indicating that a large amount of bacterial protein was produced after AM fermentation, and its nutritional value was improved. FAM had significant effects on the growth performance of tiger grouper (p < 0.05). The high-density lipoprotein cholesterol (HDL-C) was highest in L4 group, being significantly different from L0 group. The area and diameter of hepatocytes were lowest in L3 and L4, and the density of hepatocyte was highest in L4 group and relatively decreased in L5 group. The mucosal height and muscular thickness were highest in L3 group. The intestinal microbiota structure of tiger grouper was changed under the intervention of FAM. The lower abundance of potential pathogenic bacteria and higher abundance of probiotics colonization in the L4 group showed that the dose of FAM had the best effect on improving the health of intestinal microbiota. This study indicates that the addition of FAM in the feed contributes to liver health, improves intestinal morphology, and regulates the intestinal microbiota of tiger grouper. The addition ratio of 1%–2% is better for intestinal and liver health, and a high addition ratio will cause liver damage. Our work will provide a reference for the addition and management of FAM in the aquaculture industry.